2019
DOI: 10.30944/20117582.102
|View full text |Cite
|
Sign up to set email alerts
|

Intususcepción como causa de obstrucción intestinal en el adulto: un desafío para los cirujanos

Abstract: Intestinal intussusception in adults is a rare finding, with non specific symptoms and is responsible for 5% of intestinal obstructions. Pre-operative diagnosis remains a challenge for surgeons and the optimal treatment is still in debate. We present two cases of intestinal intussusception caused by different etiologies; the first is a colon-colonic intussusception caused by an adenocarcinoma, and the second is an ileo-colonic intussusception caused by a gastrointestinal stromal tumor (GIST). Both cases were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
5
0
4
Order By: Relevance
“…3 It is reported that 63% of the causes of intussusception are due to tumors, with neoplastic etiology being more common, requiring surgical management in order to reestablish intestinal transit and resect the affected segment and the lesion that is the axis of intussusception. 4 Clinical manifestations are explained in relation to intestinal occlusion, with abdominal pain being the most common presentation. 4,5 Extension studies may be requested as part of approach, with computed tomography being imaging study of choice due to its diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 It is reported that 63% of the causes of intussusception are due to tumors, with neoplastic etiology being more common, requiring surgical management in order to reestablish intestinal transit and resect the affected segment and the lesion that is the axis of intussusception. 4 Clinical manifestations are explained in relation to intestinal occlusion, with abdominal pain being the most common presentation. 4,5 Extension studies may be requested as part of approach, with computed tomography being imaging study of choice due to its diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…4 Clinical manifestations are explained in relation to intestinal occlusion, with abdominal pain being the most common presentation. 4,5 Extension studies may be requested as part of approach, with computed tomography being imaging study of choice due to its diagnostic accuracy. 4,6 Surgical management of intestinal intussusception involves resection of the affected segment and restitution of transit considering free margins and oncological approach depending on the context of each patient due to the high prevalence of malignancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La tomografía computarizada (TC) de abdomen es «el estándar de oro» (gold standard) para diagnosticar invaginación intestinal en el adulto. Además de diagnosticar, permite llegar al diagnóstico subyacente de la enfermedad (punto guía) y valorar complicaciones (obstrucción intestinal, isquemia y perforación) (7)(8)(9)(10)(11) .…”
Section: Introductionunclassified
“…En ausencia de obstrucción intestinal, la laparoscopia podría ser el método de elección para el abordaje quirúrgico. El pronóstico de la intususcepción está relacionado con la enfermedad de base (11) . Presentamos un caso de invaginación intestinal del adulto cuyo origen fue un tumor benigno de escasa localización en el tubo digestivo y con potencial de malignidad.…”
Section: Introductionunclassified